Gentamicin Induced Damage in Nephrotoxicity and Hepatotoxicity in Male Rabbits: The Protective Effect of Cinnamon - Fayrouz Alzobair,; Fadwa Nbaiwa, (AlQalam Journal of Medical and Applied Sciences, 2024)
One common aminoglycoside antibiotic that is well-known for its ability to treat gram-negative bacterial infections is gentamicin. Its nephrotoxic and hepatotoxic side effects, which are mostly brought about by the production of free radicals that harm kidney and liver cells, frequently restrict its therapeutic application. On the other hand, strong antioxidants found in cinnamon, a popular spice and therapeutic plant, have been demonstrated to have protective properties against oxidative stress. In order to assess the protective role of cinnamon, the current study examines how cinnamon affects gentamicin-induced changes in biochemical markers, liver enzymes in male rabbits. Treatment groups included a control group, a gentamicin-only (GIN) group, a cinnamon-only (CIN) group, and a combined cinnamon-gentamicin (CIN+GIN) group. The results showed that GIN group elevated liver enzymes, specifically aspartate transaminase (AST) and alanine transaminase (ALT), suggesting possible hepatotoxicity. The dose of cinnamon decreased these enzyme levels, while the combination therapy kept the AST levels close to control. Biochemical examination revealed that cinnamon reduced these alterations, particularly in the combination therapy group, while gentamicin increased total protein, urea, and creatinine levels, indicating renal and hepatic stress. The study concludes by highlighting the potential of cinnamon in reducing gentamicin-induced toxicity, specifically through its effects on lipid profiles, liver enzyme activities, body weight, blood profiles, and biochemical markers. This suggests that cinnamon could be used as an adjuvant therapy to reduce the negative effects of gentamicin". من المضادات الحيوية الشائعة من مجموعة الأمينوغليكوزيد والتي تشتهر بقدرتها على علاج الالتهابات البكتيرية سلبية الجرام الجنتاميسين. وكثيراً ما تحد الآثار الجانبية السامة للكلى والكبد، والتي تنجم في الغالب عن إنتاج الجذور الحرة التي تضر بخلايا الكلى والكبد، من استخدامها العلاجي. ومن ناحية أخرى، ثبت أن مضادات الأكسدة القوية الموجودة في القرفة، وهي من التوابل الشعبية والنباتات العلاجية، لها خصائص وقائية ضد الإجهاد التأكسدي. ومن أجل تقييم الدور الوقائي للقرفة، تدرس الدراسة الحالية كيف تؤثر القرفة على التغيرات التي يسببها الجنتاميسين في العلامات الكيميائية الحيوية وأنزيمات الكبد لدى الأرانب الذكور. وتضمنت مجموعات العلاج مجموعة تحكم ومجموعة جنتاميسين فقط ومجموعة قرفة فقط ومجموعة جنتاميسين وقرفة مجتمعة (CIN+GIN). وأظهرت النتائج أن مجموعة جين أظهرت ارتفاعًا في إنزيمات الكبد، وتحديدًا أسبارتات ترانس أمينيز (AST) وألانين ترانس أمينيز (ALT)، مما يشير إلى احتمال حدوث سمية كبدية. وقد أدت جرعة القرفة إلى خفض مستويات هذه الإنزيمات، في حين حافظ العلاج المركب على مستويات AST قريبة من السيطرة. وكشف الفحص الكيميائي الحيوي أن القرفة قللت من هذه التغيرات، وخاصة في مجموعة العلاج المركب، بينما زاد الجنتاميسين من مستويات البروتين الكلي واليوريا والكرياتينين، مما يشير إلى الإجهاد الكلوي والكبدي. وتختتم الدراسة بتسليط الضوء على إمكانات القرفة في تقليل السمية الناجمة عن الجنتاميسين، وتحديدًا من خلال تأثيراتها على ملفات الدهون وأنشطة إنزيمات الكبد ووزن الجسم وملفات الدم والعلامات الكيميائية الحيوية. وهذا يشير إلى أنه يمكن استخدام القرفة كعلاج مساعد لتقليل الآثار السلبية للجنتاميسين